PENGARUH HARAPAN KONSUMEN DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING DI ROKET CHICKEN YOGYAKARTA - Nada, Alliskha Qotrun; Nur, Annisa (Universitas Sarjanawiyata Tamansiswa, 2025)
Rocket Chicken is one of the leading local brands in the franchise fast food restaurant sector specializing in fried chicken. Rocket Chicken has implemented various policies that have enabled the company to continue growing. Business actors must strive to maintain overall product quality, service, and pricing to meet customer perceptions and expectations. When customer expectations are fulfilled and they experience satisfaction, it can lead to customer loyalty toward the company. The objective of this research is to analyze the influence of customer expectations and price perception on customer loyalty through customer satisfaction. The sample of this study consists of 104 respondents who have previously purchased Rocket Chicken products. Data was collected using a purposive sampling method by distributing questionnaires to the respondents. The research employed a causal method with a quantitative approach. Based on statistical data processing using SPSS, the results showed that, partially, customer expectations have a significant effect on customer loyalty, while price perception does not have a significant effect on customer loyalty. Simultaneously, customer expectations and price perception through customer satisfaction have an effect on customer loyalty. Furthermore, customer satisfaction is able to mediate the relationship between customer expectations and price perception on customer loyalty.